Trump Administration’s Policies towards the Palestinian-Israeli Conflict: The Culmination of Christian-Zionist alliance Impact - Ayoub, Hasan (Dirasat: Human and Social Sciences, 2021)
This study addresses the exceptional influence exerted by groups and individuals who identify with right-wing, Zionist, and Evangelical fundamentalist organizations on Donald Trump’s foreign policy decisions. The analyses presented stems for understanding America’s foreign policy in the current moment from the prospective of domestic actors. Other studies’ treatment of the impact of Zionist organizations on the subject matter withstanding, we focus on the raising unique coalition between a group of influential individuals and groups that shapes Trump’s policies on the Palestinian cause and the Palestinian-Israeli conflict. The study highlights the dual strategy of this coalition to confer legitimacy over Zionist and Christian biblical claims to the land of Palestine, coupled with a series of domestic tactics that aim to shut political opposition down.